AMIODARONE VERSUS LIDOCAINE FOR PEDIATRIC CARDIAC ARREST DUE TO VENTRICULAR ARRHYTHMIAS: A SYSTEMATIC REVIEW - M. Hadi, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Pediatric cardiac arrests are relatively uncommon but pose significant burdens. The management of pediatric cardiac arrest is unclear between amiodarone or lidocaine, necessitating further research to establish effective interventions.Aim: to systematically review the effect and funtion of amiodarone and lidocaine, whether amiodarone is more recommended or vice versa.Methods: this review conducted a thorough literature search comparing amiodarone and lidocaine for shock-refractory pVT/VF in children. Outcomes, including ROSC, termination of arrhythmia, and survival at discharge, were also evaluated.Results: Out of 756 articles, only three met inclusion criteria comparing amiodarone and lidocaine for VT/VF. One adult study favored amiodarone for survival to hospital admission, but not discharge. Another study on pediatric cases showed lidocaine improved ROSC and 24-hour survival significantly. However, evidence quality was very low for both drugs, warranting further research. A small trial in adults favored amiodarone in stable VT, but its limited size and data quality pose limitations.Conclusion: The findings of this systematic review proposes that either amiodarone or lidocaine could be considered for the treatment of pediatric shock-resistant VF/pVT.